Development of Montanide-based inactivated vaccine against duck plague virus in Bangladesh - Yasmin, Layla; Hossain, Md Juwel; Islam, Towhidul; Khan, Mohammad Ferdousur Rahman; Rahman , Marzia; Kamal, Tazrin; Nazir, K H M Nazmul Hussain; Rahman, Md Tanvir; Ahmed, Rony; Rahman, Mohammad H; Rahman, Md Bahanur (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This work aimed to develop Montanide-based inactivated duck plague (DP) vaccines from field isolates in Bangladesh and to evaluate the safety, potency, and efficacy. Materials and Methods: Suspected DP samples such as liver, spleen, trachea, and so on (N = 211) were collected from Netrokona, Mymensingh, and Kishoreganj districts. Duck plague virus (DPV) was identified through PCR and characterized by partial sequencing. Following pathogenicity tests in ducklings, the vaccine candidate virus was propagated in embryonated duck eggs and inactivated with 0.2% formalin to formulate 45% Montanide ISA 78 VG and ISA 71 VG-based vaccines. Formulated vaccines were administered following safety tests to G1 and G2, whereas G3 received 1X phosphate buffer saline. Blood samples were collected, and antibody titers were measured using an ELISA kit for up to 6 months. A challenge study was conducted to determine the potency of vaccines. Results: The prevalence rate was 65.40% (138/211) of DPV-suspected samples, where Netrokona, Mymensingh, and Kishoreganj were 67.81% (59/87), 64.61% (42/65), and 62.71% (37/59), respectively. The pathogenicity test revealed significant morbidity and mortality in ducklings. Two formulated vaccines comply with the safety criteria in ducklings. In the challenge study, both vaccinated groups (G-1, G-2) achieved 88.89% protection against the virulent DP virus, whereas the control group exhibited 93.33% mortality. The antibody titer measured by ELISA peaked at 21 days and remained till 180 days post-vaccination, which showed a 0.1% (p < 0.001) level of significance. Conclusion: After 6 months of vaccination, the Montanide ISA 78 VG-based vaccine showed slightly higher immunogenicity than ISA 71, though both were demonstrated to be safe against the DP virus. J. Adv. Vet. Anim. Res., 12(3): 1070–1080, September 2025 http://doi.org/10.5455/javar.2025.l967